2001
DOI: 10.1002/1529-0131(200106)44:6<1401::aid-art234>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Host metalloproteinases in Lyme arthritis

Abstract: Objective : To assess the role of matrix metalloproteinases (MMPs) in cartilage and bone erosions in Lyme arthritis Methods We examined synovial fluid from 10 patients with Lyme arthritis for the presence of MMP‐2, MMP‐3, MMP‐9, and “aggrecanase” activity using gelatinolytic zymography and immunoblot analysis. We developed an in vitro model of Lyme arthritis using cartilage explants and observed changes in cartilage degradation in the presence of Borrelia burgdorferi and/or various protease inhibitors. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 53 publications
3
59
0
Order By: Relevance
“…It has been previously shown that B. burgdorferi, unlike most other bacteria that cause septic arthritis, does not produce collagenases or other enzymes capable of destroying joint extracellular matrix (5,18). Instead, we have shown that cartilage degradation in Lyme arthritis is due to induction of a class of host enzymes called matrix metalloproteinases (MMPs) (13,20). All MMPs share a common function of extracellular matrix degradation (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that B. burgdorferi, unlike most other bacteria that cause septic arthritis, does not produce collagenases or other enzymes capable of destroying joint extracellular matrix (5,18). Instead, we have shown that cartilage degradation in Lyme arthritis is due to induction of a class of host enzymes called matrix metalloproteinases (MMPs) (13,20). All MMPs share a common function of extracellular matrix degradation (8).…”
mentioning
confidence: 99%
“…Two MMPs in particular, collagenase-1 (MMP-1) and stromelysin-1 (MMP-3), were found to be elevated in the synovial fluid of patients with Lyme arthritis (20). In vitro models of Lyme arthritis confirmed the ability of B. burgdorferi to induce these MMPs from human chondrocytes (HCs) and the ability of MMP inhibitors to block B. burgdorferi-induced cartilage degradation (13).…”
mentioning
confidence: 99%
“…Hu and co-workers [11] studied the involvement of MMPs in cartilage and bone erosions in LA. They examined synovial fluid from patients with LA for MMP-2, MMP-3 and MMP-9.…”
Section: Figure 4 (A)mentioning
confidence: 98%
“…MMP-1, MMP-3, MMP-8 and -9 have been found in synovial fluid of Lyme arthritis (LA) patients [7]. Different MMPs (MMP-1, 2, -3,-10, -13, and -19) have been shown to be induced in different ways in human and murine LA [3,11]. Lin and colleagues [7] found that the levels of synovial MMPs, also MMP-8, were significantly higher in antibiotic treatment resistant patients.…”
Section: Introductionmentioning
confidence: 99%
“…18 Particularly relevant to the present study, elevated levels of MMP-9 have been observed in the erythema migrans lesions and cerebrospinal and synovial fluid of patients with Lyme disease. [21][22][23][24] Once secreted, MMP-9 cleaves the ECM, thus facilitating cell migration through a normally dense fibrillar environment. In addition to fostering general leukocyte movement, degradation of collagen also liberates small tripeptide fragments such as proline-glycine-proline (PGP), which exhibit an affinity for the chemokine receptors CXCR1/2 as do the neutrophil chemoattractants CXCL8/KC and MIP-2.…”
mentioning
confidence: 99%